Diseño de circuito de media tensión para alimentar el corregimiento de San José de Oriente (Cesar) (2013)
The distribution of electricity is vital in the process from the generation to commercialization of the same. That is where it becomes the voltage level from medium to low voltage, it means, allowing the transformation of energy to the last use by users. The design of a medium-voltage circuit is performed to improve the power distribution system or to encompass lands not energize nowadays. This work provides a detailed design level of a medium voltage circuit to the village of San Jose de Oriente located in the north of the department of Cesar which has consistently had problems with the quality of electricity service due to voltage fluctuations generated by the long distances required by the circuit that energizes the whole region now. This design is based on current legislation NTC 2050 and RETIE for constructions of overhead distribution lines.